Wheat germ agglutinin-conjugated liposomes incorporated with cardiolipin to improve neuronal survival in Alzheimer’s disease treatment - Kuo YC (Dove Medical Press, 2017)
Yung-Chih Kuo,1 Che-Yu Lin,1 Jay-Shake Li,2 Yung-I Lou3 1Department of Chemical Engineering, 2Department of Psychology, National Chung Cheng University, Chia-Yi, 3Department of Accounting, Providence University, Taichung, Taiwan, Republic of China Abstract: Curcumin (CRM) and nerve growth factor (NGF) were entrapped in liposomes (LIP) with surface wheat germ agglutinin (WGA) to downregulate the phosphorylation of kinases in Alzheimer’s disease (AD) therapy. Cardiolipin (CL)-conjugated LIP carrying CRM (CRM-CL/LIP) and also carrying NGF (NGF-CL/LIP) were used with AD models of SK-N-MC cells and Wistar rats after an insult with β-amyloid peptide (Aβ). We found that CRM-CL/LIP inhibited the expression of phosphorylated p38 (p-p38), phosphorylated c-Jun N-terminal kinase (p-JNK), and p-tau protein at serine 202 and prevented neurodegeneration of SK-N-MC cells. In addition, NGF-CL/LIP could enhance the quantities of p-neurotrophic tyrosine kinase receptor type 1 and p-extracellular signal-regulated kinase 5 for neuronal rescue. Moreover, WGA-grafted CRM-CL/LIP and WGA-grafted NGF-CL/LIP significantly improved the permeation of CRM and NGF across the blood–brain barrier, reduced Aβ plaque deposition and the malondialdehyde level, and increased the percentage of normal neurons and cholinergic activity in the hippocampus of AD rats. Based on the marker expressions and in vivo evidence, current LIP carriers can be promising drug delivery systems to protect nervous tissue against Aβ-induced apoptosis in the brain during the clinical management of AD. Keywords: liposome, Alzheimer’s disease, β-amyloid, neurodegeneration, blood–brain barrier, wheat germ agglutinin